1971
DOI: 10.1104/pp.47.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Ribosomal Ribonucleic Acid and Fraction I Protein in Wheat Leaves

Abstract: In light-grown wheat (Triticumn aestivum L.) seedlings, the amount of chloroplast and cytoplasmic ribosomal RNA increased to a maximum in the first leaf near the end of its growth and declined by about 60% in the following 3 days. While total ribosomal RNA was declining, labeled uracil was still incorporated into cytoplasmic ribosomal RNA, but the rate of incorporation into chloroplast ribosomal RNA fell by more than 80%, as did the incorporation of labeled leucine into fraction I protein. Either there is grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Active synthesis of RuBPCase in the distal section of mature leaves has also been reported in wheat (7). These two cases stand in contrast to the marked reduction in incorporation of labeled precursors into carboxylase in a number of other plant species at about the time that leaf expansion ceases (8,9,24).…”
mentioning
confidence: 76%
“…Active synthesis of RuBPCase in the distal section of mature leaves has also been reported in wheat (7). These two cases stand in contrast to the marked reduction in incorporation of labeled precursors into carboxylase in a number of other plant species at about the time that leaf expansion ceases (8,9,24).…”
mentioning
confidence: 76%
“…Marked variations in physiological activity with leaf maturation and aging have been reported, including changes in photosynthesis and photosynthate translocation (2,3,12,14,24), photorespiration (10,21), protein and enzyme synthesis (4,6,8,15,24,26), and nucleic acid metabolism (17,19,23,26). Our understanding of leaf developmental physiology, however, remains rudimentary.…”
mentioning
confidence: 99%
“…Although protein synthesis capacity remained high in apple leaf tissue, the total and specific activities of some enzymes, such as TDH(NAD)' and TDH(NADP), began to decline when total protein declined (19) and photosynthetic capacity in other leaf types also occurs at the time of initial protein decline, the onset of senescence (7,10,11,17). It has been suggested that the initial decline of protein and the concurrent loss of activity and lack of incorporation of "4C-amino acids into fraction I protein and other enzymes is due to the cessation or reduction of chloroplastic protein synthesis (2,12,23).…”
mentioning
confidence: 99%